Assessment of companies’ safety processes maturity in requirements engineering with Uni-REPM SCS - Vilela, Jéssyka; Martins, Luiz Eduardo G.; Gorschek, Tony; Castro, Jaelson (Anais Estendidos do Congresso Brasileiro de Software: Teoria e Prática (CBSoft), 2020)
Safety is an important quality attribute in the development of safety-critical systems (SCS). This attribute can be achieved by improving safety processes maturity to reduce accidents and safety incidents. In this work, we present a safety module called Uni-REPM SCS for the Uni-REPM maturity model. We describe the methodology used to develop the module, how we built and validated it and further research and possibilities of collaboration.